Antiplasmodial activity of two fractions obtained from n-hexane extract of Garcinia parvifolia Miq stem bark - Syamsudin .; Soesanto Tjokrosonto; Subagus Wahyuono; Mustofa . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Antiplasmodial activity of fractions A and B obtained from n-hexane extract of stem bark of Garcinia parvifolia have been evaluated. The in vitro antiplasmodial activity was investigated on two strains of Plasmodium falciparum, FCR-3 a chloroquine resistant and D10, a chloroquine sensitive strains and their antiplasmodial activity was expressed by the concentration inhibiting 50.% of the parasite growth (IC50). The results showed that the fractions A and B were active against P. falciparum with the IC50 values of 2,79 ± 0,10 μg/mL and 12,30 ± 1,21.μg/mL on FCR-3 strain and 1,52 ± 0,24.μg/mL and 4,66 ± 1,24 μg/mL on D10 strain. Identification of active constituents in the both fractions showed the existence of triterpenoide, steroide and flavonoide compounds.Key words: Antiplasmodial activity , Garcinia parvifolia, active constituents.